KONTRIBUSI USAHATANI LAHAN SURUTAN BENDUNGAN SERBAGUNA WONOGIRI TERHADAP KESEJAHTERAAN RUMAH TANGGA PETANI PENYEWA LAHAN SURUTAN - Emi Widiyanti; Marcelinus Molo; Bekti Wahyu Utami (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2012)
ABSTRACTThis study aimed to examine the effect of farming in the drawdown area of the Multi-purpose dam of Wonogiri to the welfare of the farmers and their families. About 63 farmers who engaged in a contractual arrangement with PT. Jasa Tirta I, represented by the Division IVwere selected for the field survey and interviews. The compelemntary data was collected through a series of Focus Group discussins (FGD)The study indicates that (a) the drawdown farming contributes 25,54% to the annual household income which is higher than the contribution of the farming outside the drawndown area. A large amount of drawndown income is primarily contributed by the corn aside from paddy and soybean; (b) the drawdown farming offers 28,11% to the total expenses of the household food consumption in a cropping season. This figure is higher than the contibution offered by farming outside the drawdown site, that is about 26,09%. Keywords: farming in the drawdown area of Multipurpose dam, income contribution